Periwayatan Hadis Nabi (Tahammul wal Ada’), Ilmu Jarh wa Ta’dil dan Ilmu Nasikh Mansukh dalam Hadis - Dina Sakinah Wijaya; Nurul Fitri Habibah (El-Sunnah)
The amount of hoax information makes us obliged to carefully examine the information we get. In understanding a hadith, we must examine the process of narrating the hadith so that the book of isa knows the validity of the hadith. The purpose of this study is to find out the science related to hadith passage, jarh wa ta'dil science and nasikh Mansukh science. This research is a Library Research. The result of this research is the activity of tahammul and ada' al-hadith is the process of narrating hadith either accepting or conveying it which is deliberately carried out by periwayats scientifically using certain theories and methods for the preservation of hadith. The science of jarh wa ta'dil is a science that addresses in it the judgments of good and bad/defective of a critic of rawi hadith. Meanwhile, nasikh wa al-mansukh is defined as the science that discusses conflicting hadiths, which cannot possibly be compromised, by specifying some of them, as 'nasikh' and others as 'mansukh'.